Improving the English vocabulary of elementary school students through the Marbel Learn English application with the EMRED approach - Nurcahyani, Nicky; Salim, Herli (International Conference on Education in Primary and Early Childhood, Marine, Computer Information, and Logistics, 2025)
English is one of the foreign language subjects that students learn at school. Introduction to vocabulary is the initial stage given to students in learning English. However, students' vocabulary is still limited, this is because students have difficulties in learning English. So students need the right media and learning approach. In this study, the researcher used the Marbel Learn English application  with the EMRED Approach which aims to determine its effect on improving the English vocabulary of third grade students of SDN Cikuda 01. This research is a quantitative research with an experimental type of research. The subjects in this study are grade III students of SDN Cikuda 01 which totals 60 students. Researchers collected data by conducting tests, interviews and distributing questionnaires to find out the students' responses to  the treatment that had been given. The results of this study show that the influence of the use of the Marbel Learn English application  with the EMRED Approach on improving students' English vocabulary, this is shown from the average post-test score  in the control class of 67.33 and the experimental class of 81.00, and the results of the Independent Sample T Test have a value of Sig. (2-tailed)) = 0.001 < 0.005. The results of the student response questionnaire had an average result of 84.08% with the very good category. It can be concluded that the use of the Marbel Learn English application  with the EMRED Approach is very well used to improve students' English vocabulary.
Keywords: english; marbel learn english application; emred approach; vocabulary improvement